China’s “New Regionalism” as a Mechanism to Strengthen the Influence of China in the Global Integration Processes: An Example of Eurasian Economic Union - Kolpakova, Tatyana V.; Kuchinskaya, Tatiana N. (International Journal of Economics and Financial Issues, 2015)
The article presents an analysis of the role of the Chinese factor in global integration processes carried out in the context of the Eurasian Economic Union (EAEU). It is proven that a key mechanism to strengthen the role of China in the EAEU, and other integration associations, is the strategy of the China’s ‘New Regionalism’, according to which the Chinese government is using economic, political, ideological and cultural development strategies provides a ‘soft’ economic expansion. The essence of China’s ‘New Regionalism’ is its desire for a multipolar world based on the principles of non-interference policy, and the formation of supranational and transnational integration groupings to strengthen their economic potential. At the core of the China’s interest towards EAEU initiated by Russia lie the factors such of geopolitical, economic and security nature, as well as the interest in the project ‘The economic times of the Silk Road’. The proximity of the goals of these initiatives highlights the issue of a possible competition between the two countries in the struggle for strategic resources of the Central Asian region. It is concluded that the projects of China and Russia being implemented do not have the rivalry potential, but rather complement and reinforce each other. Moreover, the deepening of the strategic partnership between the two countries based on the principles of co-development will contribute to the successful promotion of the process of regional integration, not only in Central Asia but also in the Asia Pacific region. It emphasizes that the underestimation of the specifics of the China’s ‘New Regionalism’ by the Russian counter side might lead to a lowering of its competitive advantages in the process of implementation of joint programs and projects. Keywords: China’s New Regionalism, Central Asia region, Asia Pacific region, Eurasian Economic Union JEL Classifications: E6; F5